2018
DOI: 10.1111/joss.12478
|View full text |Cite
|
Sign up to set email alerts
|

Application of two projective techniques in the study of consumer perception of antiperspirant/deodorants

Abstract: The present study aimed to identify the main aspects involved in consumers' perception of four types of antiperspirants/deodorants (APDs); cream, aerosol, roll‐on and stick; and compared the findings by using projective techniques; word association (WA) and product personality profiling (PPP) tasks. To apply the PPP task, participants had to imagine that each type of APDs was a person and describe it by gender, age, marital status, children, physical complexion, personality, work/profession/occupation, transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…A sensory evaluation measures the physiological response to a stimulus, minimizing influences presented by psychological factors, such as culture, age and environmental aspects. The literature shows various studies involving sensory studies, for example, the main aspects involved in the consumers perception with different antiperspirants and deodorants (cream, aerosol, roll-on, and stick), comparing whether the concept of effectiveness by the consumer is explained only by the duration of the effect or if it integrates other components 18 . David et al 19 investigated the affective and brain effects of using a rose-scented cosmetic cream and observed that the scented cream over the odorless cream increased the positive affective states (more relaxation, satisfaction, happiness) and reduced reactivity associated with the threat and negative stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…A sensory evaluation measures the physiological response to a stimulus, minimizing influences presented by psychological factors, such as culture, age and environmental aspects. The literature shows various studies involving sensory studies, for example, the main aspects involved in the consumers perception with different antiperspirants and deodorants (cream, aerosol, roll-on, and stick), comparing whether the concept of effectiveness by the consumer is explained only by the duration of the effect or if it integrates other components 18 . David et al 19 investigated the affective and brain effects of using a rose-scented cosmetic cream and observed that the scented cream over the odorless cream increased the positive affective states (more relaxation, satisfaction, happiness) and reduced reactivity associated with the threat and negative stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The red light influenced evaluations by the participants and affected the description of the tested products. Another way to improve the assessment is word association (WA) and the product personality profile (PPP), which can be used independently or complementarily (Gámbaro et al, 2019). WA provides information on the characteristics of the different formulations and the product's personality profile (PPP) gives information about the image consumers have of each product.…”
Section: Acceptance and Purchase Intentionmentioning
confidence: 99%
“…Word Association technique was explored by Gámbaro, Roascio, Boinbaser, Pérez, and Parente () and Gámbaro, Parente, Roascio, and Boinbaser (). Product Personality Profiling was applied by (Gámbaro et al, ). Check all that apply (CATA) was explored in cosmetics description by Parente et al () and Parente, Emma, Manzoni, and Ares ().…”
Section: Introductionmentioning
confidence: 99%
“…Successful results using consumers to describe, profile, and differentiate new cosmetic products can be found in the literature. Word Association technique was explored by Gámbaro, Roascio, Boinbaser, Pérez, and Parente (2018) and Gámbaro, Parente, Roascio, and Boinbaser (2014). Product Personality Profiling was applied by (Gámbaro et al, 2018).…”
mentioning
confidence: 99%